Electrical capacitance volume tomography for human brain motion activity observation - Taruno, Warsito P.; Ihsan, Muhammad F.; Baidillah, Marlin R.; Tandian, Timothy; Mahendra, Mahdi; Aljohani, Mohammed (IEEE transactions on biomedical engineering, 2014)
In this study we performed brain activity observation related to simple tasks of executed movement (EM) and imagined movement (IM) using Electrical Capacitance Volume Tomography (ECVT). ECVT has been previously applied to brain activity imaging and brain cancer detection. This study is intended to elaborate further the previous studies on the brain functional imaging. Experiment on human subjects was conducted by measuring brain signals using ECVT during five conditions: (1) relax: baseline condition, (2) actual movement with the right hands and left hands, (3) imagined movement with right and left hands. Signal normalization was used to extract the ECVT brain activity signals related to a particular condition. Qualitative and quantitative analysis was performed on the ECVT images of brain activity related to EM and IM tasks. The results indicate that lateral brain activation can be observed using ECVT in concordance with fMRI studies.